PEMANFAATAN APLIKASI TIKTOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SEJARAH KEBUDAYAAN ISLAM DI KELAS X SEKOLAH MENENGAH ATAS MUHAMMADIYAH 3 WATUKELIR TAHUN AJARAN 2023/2024 - Fatonah Irani Sholihah; Suhadi Suhadi; Yetty Faridatul Ulfah (STKIP Pesisir Selatan, 2025)
The rapid development of digital technology has transformed learning paradigms, including within Islamic education. This study was motivated by the low learning motivation of students in the subject of Islamic Cultural History (Sejarah Kebudayaan Islam) at Muhammadiyah 3 Watukelir Senior High School, which traditionally relied on conventional teaching methods. The purpose of this research is to analyze the use of TikTok as a learning medium to enhance student motivation, identify obstacles encountered, and propose effective solutions for its optimization. This research applied a qualitative descriptive method using observation, interviews, and documentation techniques involving SKI teachers and tenth-grade students. Data analysis followed Miles and Huberman’s interactive model, consisting of data reduction, presentation, and conclusion drawing. The findings revealed that TikTok effectively increases students’ motivation and engagement through creative and educational video content. The main challenges include unstable internet connections and limited availability of appropriate educational materials, which can be addressed by improving school facilities, providing teacher training, and producing self-made Islamic learning videos. The implication of this research emphasizes that TikTok can serve as an innovative learning medium that harmoniously integrates digital technology with Islamic educational values in a creative and meaningful way.